2017
DOI: 10.1021/acssuschemeng.7b01830
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Magnetic Porous Cellulose-Based Nanocomposite Films Prepared by a Green Method

Abstract: The present work expands our previous studies related to cellulose processing with room-temperature ionic liquids and simultaneous integration of functional nanoparticles toward photocatalytically active and easily recyclable nanocomposite porous films based on a renewable matrix material. Porosity can be tuned by the selection of phase separation conditions for the films obtained from the casting solutions of cellulose in ionic liquids or their mixture with an organic cosolvent. TiO 2 nanoparticles confer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…Figure a illustrates the FTIR spectra of the wood pulp and NCF-1.8. The peak of wood pulp at 1432 and 1120 cm –1 assigned to the cellulose I crystal exhibited a sharp drop in NCF-1.8. , The wood pulp exhibited three crystal peaks (Figure b) of 14.8, 16.3, and 22.6°corresponded to crystal planes (11̅0), (110), and (020) of cellulose I . The regenerated cellulose fibers displayed three crystal peaks at 12.1, 19.8, and 22.0° assigned to the crystal planes (11̅0), (110), and (020) of cellulose II. , These results demonstrated that the crystal structure of the cellulose fibers transformed from cellulose I to cellulose II during the filament production process.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure a illustrates the FTIR spectra of the wood pulp and NCF-1.8. The peak of wood pulp at 1432 and 1120 cm –1 assigned to the cellulose I crystal exhibited a sharp drop in NCF-1.8. , The wood pulp exhibited three crystal peaks (Figure b) of 14.8, 16.3, and 22.6°corresponded to crystal planes (11̅0), (110), and (020) of cellulose I . The regenerated cellulose fibers displayed three crystal peaks at 12.1, 19.8, and 22.0° assigned to the crystal planes (11̅0), (110), and (020) of cellulose II. , These results demonstrated that the crystal structure of the cellulose fibers transformed from cellulose I to cellulose II during the filament production process.…”
Section: Resultsmentioning
confidence: 97%
“…The peak of wood pulp at 1432 and 1120 cm −1 assigned to the cellulose I crystal exhibited a sharp drop in NCF-1.8. 39,40 The wood pulp exhibited three crystal peaks (Figure 5b) of 14.8, 16.3, and 22.6°corresponded to crystal planes (11̅ 0), (110), and (020) of cellulose I. 41 The regenerated cellulose fibers displayed three crystal peaks at 12.1, 19.8, and 22.0°assigned to the crystal planes (11̅ 0), (110), and (020) of cellulose II.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In situ incorporation Ex situ incorporation Iron oxide Co-precipitation in cellulose matrix: cellulose suspension, 47,48,51 cellulose solution 49,50,[56][57][58] Preformed particles: added to cellulose solution; 49,[52][53][54][55][59][60][61][62] surface modification of cellulose prior; 63 using a retention aid 71 Hydrothermal methods 68…”
Section: Magnetic Moietymentioning
confidence: 99%
“…56,57 Cellulose xanthate, that is a soluble intermediate in viscose production and can be regenerated to cellulose, was functionalized with iron oxide particles by adding premade particles as well as in a one-step synthesis by adding an iron source into the xanthate solution. 49 Furthermore, ionic liquids are a rather new class of cellulose solvents, which are already being used in preparing magnetically functional cellulose: ionic liquids have been used to dissolve the cellulose and iron salts for co-precipation, 58 mixing together, [59][60][61][62] or grafting 63 the cellulose and magnetic component. Ionic liquids were also used as a solvent for dissolution and regeneration in the sol-gel transition method to produce cellulose-chitosan magnetic composites.…”
Section: Nickelmentioning
confidence: 99%
“…Son yıllarda atıksu arıtımında boya giderimi üzerine yapılan çalışmalarda, TiO 2 fotokatalizörün polimer matrikse tutturularak kullanımının önemine dikkat çekilmiştir. Literatürde, polidisiklopentadien/TiO 2 [8], düşük yoğunluklu polietilen/TiO 2 ve yüksek yoğunluklu polietilen/TiO 2 [7], selüloz/TiO 2 [9], poli(metil metakrilat)/TiO 2 [5], hidroksiapetit/poliakrilat/ TiO 2 [10], politetrahidrofuran-üretan dimetakrilat/TiO 2 [11], polipirol/TiO 2 [12] ve poli (3-heksiltiyofen)/TiO 2 [13] kompozit sistemlerinin fotokatalitik etkinliği çalışılmıştır. Belirtilen polimer matrikslerindeki TiO 2 fotokatalizörünün fotokatalitik etkinliği, model boyanın su ortamında bozunması ile tespit edilmiştir.…”
Section: Giriş (Introduction)unclassified